The concept and importance of settlement agreements in commercial proceedings - M. Ye. Vasylenko (Bulletin of Kharkiv National University of Internal Affairs)
The article establishes that a settlement agreement in commercial proceedings is a voluntary agreement between the parties to a conflict to resolve a dispute which arose between them in the course of conducting economic activity or in the course of performance of economic contracts. Such an agreement may be concluded both before the dispute is resolved in court and directly during the court proceedings. It is an effective means of dispute resolution, as it avoids lengthy and costly court proceedings and ensures a more prompt resolution of the problem on the merits between the parties to the conflict.